A systematic literature review on road infrastructure indicators based on distance and the effect on affordability of housing / Mohd Muhamad Hilmi Mohamad @ Masri ... [et al.] - Mohamad @ Masri, Mohd Muhamad Hilmi; Sa'ad, Mohd Farid; Aliasak, Mohd Hasrol Haffiz; Md Wadzir, Mohamad Fitry; Mohd Lazi, Mohd Khairul Afzan; Azman, Najma (2022)
This systematic review article focuses on the road infrastructure indicators based on distance, and explores into its ability to affect house prices within the context of the Malaysian property market. Most of the past researches conducted on this topic were mostly from the engineering perspective, not from Asian region and seldomly being conducted on the basis of built environment perspective. This provides a basis for the researchers in deciding ultimately on how this can affect the public's ability in purchasing affordable houses. The researchers intend to outline the road infrastructure indicators based on distance and affordability of housing as this paper's aim. The objective of this paper is to provide the indicators as basis for further measurement on prices of affordable housing. The methodology for this review paper is via the implementation of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), and two main journal databases were utilized that were Web of Science and Scopus. From the considerable number of past researches obtained and the systematic review conducted, the researchers has extracted seven main themes, namely traffic number, cost of commute, vehicle mobility, travel time, workplace distance, road network distance and houses desirability. Based on the findings of the main themes, several recommendations for further research were then highlighted at the end of the review paper which include utilizations by various stakeholders in determining affordable housing, with the improvement relating to road infrastructure indicators in the context of Malaysia. The themes were then expected to become the basis for future data collection process by the researchers.